Structure prediction of the protein ccr5 delta 32 and structure comparison with ccr5 - GOPALUNI SAI AKASH, (International Journal of Pharma and Bio Sciences, 2016)
Human immunodeficiency virus (HIV) is an obligate intracellular parasite of the CD4+ T-cells. This virus targets and kills helper T cells that play a vital role in immune response. Studies have shown that the interaction between the viral glycoprotein and host proteins like CD4 and Chemokine receptor type 5 (CCR5) enable the virus to get into the helper T cells. There exists a mutant form of the protein CCR5 called the CCR5 delta 32 or CCR5-D32 which does not interact with the viral glycoprotein in the same way as CCR5 does and hence, individuals carrying this mutation are resistant to HIV infection. Here I have predicted the structure of CCR5-D32 using Modeller 9.16. Structure alignment and active site analysis revealed that, though both CCR5 and CCR5-D32 had a similar structure, their active site makeup was different and thus their functions can be different. It was also observed that the mutant lacked a few amino acids like Tyr 187, Gln 188, Lys 191, Gln 194 and Thr 195 in its active site which were lost due to the frame-shift mutation.